Effect of oil phase properties on peptide release from water-in-oil-in-water emulsions in gastrointestinal conditions. (July 2019) - Giroux, Hélène J.; Shea, Rachel; Sabik, Hassan; Fustier, Patrick; Robitaille, Gilles; Britten, Michel
Abstract: β-Lactoglobulin hydrolysate was encapsulated in water-in-oil-in-water (W1 /O/W2 ) emulsions. The effects of digestible (linseed) and non-digestible (jojoba and mineral) oil phases on emulsion characteristics and peptide release in gastrointestinal conditions were compared. Peptide release was studied at gastric pH (3) and intestinal pH (7) in the absence of lipase and at intestinal pH (7) in the presence of lipase. Released peptides were analyzed by RP-HPLC and identified by LC-MS. The encapsulation efficiency of the three emulsions was over 90%. The W1 /O/W2 emulsion produced from mineral oil had the highest droplet diameter. In the absence of lipase, the proportions of peptides released after 4 h of agitation (37 °C) were significantly lower at gastric pH (4.1%–18.8%) than at intestinal pH (10.6%–35.3%) and varied in the order mineral oil < linseed oil < jojoba oil. Peptide release was inversely correlated to oil viscosity and increased with peptide hydrophobicity. As expected, linseed oil was degraded by lipase at intestinal pH, and peptide release reached 100%. Jojoba and mineral oils were not degraded by lipase, and the proportion of released peptides was similar to that observed in the absence of lipase. Highlights: Peptide release varied in the order mineral oil < linseed oil < jojoba oil. Peptide release was inversely related to oil phase viscosity. Peptide release was lower at gastric pH than at intestinal pH. Specific peptide release increased with the increase in peptide hydrophobicity. Oil digestibility controls peptide release by lipolytic degradation of the emulsion.